An unusual case of Salmonella Enteritidis causing pneumonia, septic shock and multiple organ failure in an immunocompetent patient. (2016) - Thompson Bastin, M.L.; Neville, N.R.; Parsons, R.E.; Flannery, A.H.; Tennant, S.J.; Johnson, C.A.
Abstract: Salmonella species are facultative intracellular pathogens that most frequently cause self-limiting gastrointestinal disease, often acquired through the ingestion of contaminated food. We report the case of a 33-year-old otherwise healthy, not overtly immunosuppressed, man who was transferred to our facility with the chief complaint of respiratory failure and septic shock. Computed tomography of the chest revealed multifocal pneumonia in both lungs. A bronchial alveolar lavage was performed in the right middle lobe and cultures predominantly grew Salmonella enterica serovar Enteritidis. The patient received a prolonged course of antimicrobials, ultimately changing to oral levofloxacin. The etiology of the salmonella infection likely occurred through an aspiration event. Salmonella species are not a typical respiratory pathogen in immunocompetent hosts; however, clinicians should be aware of the possibility that salmonella species may be a pathogenic source of infection in the lungs; a prolonged course of antimicrobials may be warranted.